Peningkatan Kompetensi Profesional Guru SMA di Daerah 3T Melalui Pelatihan Penyusunan Laporan Penelitian Tindakan Kelas - Sa’o, Sofia; Meke, Konstantinus Denny Pareira; Bala, Alexander; Welu, Felix; Nande, Marsel; Daud, Maimunah Haji; Kaleka, Melkyanus Bili Umbu; Amrin, Sayful; Ma, Stefanus Hubertus Gusti; Ota, Maria Kristina; et al. (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to increase the knowledge and competence of high school teachers in one of the 3T areas in compiling classroom action research (CAR) reports. This service method used training with stages, namely assistance in making proposals, choosing the right model in implementing classroom action research and designing learning activities and tools. These service partners were junior and senior high school teachers in Nangapanda Ende District, NTT. The instrument for evaluating this activity used a pretest, and the posttest was analyzed descriptively. This service showed that the teachers’ insight increased in preparing class action research reports, and they better understood the stages in the CAR implementation process. These namely teachers were able to understand knowledge about CAR from the four indicators that were the focus of this training, including the steps for implementing CAR, the systematics of writing/composing CAR, success indicators, data analysis, and CAR implementation instruments. Implementing this training activity provides a good understanding of teachers’ understanding and professional competence regarding the importance of carrying out CAR.Â